THE INVISIBLE HANDS IN THE PRODUCTION OF GHANA’S PREMIUM COCOA: WOMEN AS KEY CONTRIBUTORS - Akolgo, Tania Ayine; Bakang, John-Eudes Andivi; Tham-Agyekum, Enoch Kwame (Applied Studies in Agribusiness and Commerce, 2024)
So often, what women do especially in relation to productive work is ignored by various researchers. This study tries to bring to the limelight the extent to which women are contributing to the production of Ghana’s premium cocoa which is an envy all over the world. A cross-sectional data from 400 women cocoa farmers in Mampong and Tepa Cocoa Districts in the Ashanti Region of Ghana was taken. Data were collected through the use of structured questionnaires. Descriptive and inferential statistics such as percentages, mean, standard deviations, frequencies, multiple linear regression were used for the data analysis. Findings from the study showed that women cocoa farmers play enormous role in the production of cocoa. They play roles in both the pre-harvest stage, and in the post-harvest stage. The results show that women in partnership with their spouses play more active role in cocoa production than women who are sole owners. Marital status, farming experience and educational level are the key factors influencing women farmers production roles. Again, marital status, pre-planting and harvesting activities influence women farmers’ access to resources, privilege, power, and control. Women farmers in partnership with their spouses face the challenge of support from their husbands while women operating as sole owners face the challenge of high cost of labour. Results prove that women cocoa farmers must be massively supported by key stakeholders in the cocoa value chain in order to make them count.